Roles of the amyloid precursor protein family in the peripheral nervous system - Caldwell, John; Klevanski, Maja; Saar, Martina; Müller, Ulrike C. (Mechanisms of development, 2013)
Compelling evidence from in vivo model systems within the past decade shows that the APP family of proteins is important for synaptic development and function in the central and peripheral nervous systems. The synaptic role promises to be complex and multifaceted for several reasons. The three family members have overlapping and redundant functions in mammals. They have both adhesive and signaling properties and may, in principle, act as both ligands and receptors. Moreover, they bind a multitude of synapse-specific proteins, and we predict that additional interacting protein partners will be discovered. Transgenic mice with modified or abolished expression of APP and APLPs have synaptic defects that are readily apparent. Studies of the neuromuscular junction (NMJ) in these transgenic mice have revealed molecular and functional deficits in neurotransmitter release, in organization of the postsynaptic receptors, and in coordinated intercellular development. The results summarized here from invertebrate and vertebrate systems confirm that the NMJ with its accessibility, large size, and homogeneity provides a model synapse for identifying and analyzing molecular pathways of APP actions.
Available online: 29 November 2012
Gesehen am 08.02.2021